Impact of rising temperatures on historical wheat yield, phenology, and grain size in Catalonia - Gulino, Davide; Sayeras, Roser; Serra, Joan; Betbese, Josep; Doltra, Jordi; Gracia-Romero, Adrian; Lopes, Marta S. (Frontiers in Plant Science, 2023)
Genetic yield progress was calculated as the slope of the linear regression function between the average yield changes of newly released and benchmark varieties between 2007 and 2021 in Catalonia, Spain. Genetic yield was stagnant for spring wheat (SW) and increased linearly by 1.31% per year for winter wheat (WW). However, a quadratic function also significantly fitted the genetic yield progress in WW, suggesting a plateau in recent years. The observed stagnation in SW yield can likely be ascribed to the gradual decline in plant height over time, which has fallen below the optimal thresholds, consequently imposing source limitations. Furthermore, the positive trend in genetic yield progress witnessed in the case of WW is potentially linked to a historical increase in both hectoliter weight (HLW) and grain number (NG). Weather analysis confirmed the potential influence of increasing temperatures in the Catalonia region at a rate of 0.050 °C per year. Moreover, climate change has been linked to an adverse impact on DH and HLW, as indicated by negative correlations with minimum (Tm), average (TA), and maximum (TM) temperatures. On average, for each °C increase in annual minimum and average temperature, a reduction of 8.2 and 12.5 days in DH was observed in SW and WW, respectively. Moreover, for each °C increase in annual average and minimum temperature a reduction of 3.1 and 6.9 kg hL-1 was observed in HLW in SW and WW, respectively. In addition, the temperatures in February, April, and May were negatively correlated with DH and HLW in both SW and WW. Optimal phenology and plant height for regional adaptation has been determined and fixed in the past, however with current climate change scenarios, these key traits must be re-accessed. These findings suggest that to enhance yield resilience in new wheat varieties amidst climate change, breeding programs should prioritize phenological adjustments aligned with optimal sowing dates, optimal plant height, along with efforts to increase HLW and grains per unit area.